Factors Influencing Language Anxiety Among Indonesian EFL Learners: Student Perspectives - Putra, Pandu Perdana; Kariadi, Mustasyfa Thabib (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
This study delves into the multifaceted nature of language anxiety among Indonesian EFL learners, focusing on the intricate interplay of individual, classroom, and socio-cultural factors. Employing a mixed-method approach, data were gathered through comprehensive surveys and in-depth interviews with students from various educational backgrounds. The Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz et al., (1986) was utilized alongside thematic analysis to identify key anxiety-inducing elements. The findings reveal that individual factors, such as self-esteem, fear of negative evaluation, and previous language learning experiences, significantly impact learners’ anxiety levels. The classroom environment, particularly the quality of teacher-student interactions, peer relationships, and teaching methods, also emerged as critical in shaping language anxiety. Furthermore, socio-cultural influences, including societal expectations, language-related stigma, and the perceived status of the English language in Indonesia, were found to intensify anxiety. This study underscores the necessity of fostering supportive and inclusive learning environments to mitigate anxiety and facilitate effective language acquisition. Ethical considerations were rigorously adhered to, ensuring participant anonymity and confidentiality. These insights offer valuable implications for educators and policymakers in crafting targeted interventions to address language anxiety.